Methods to predict variations of lower explosion limit associated with hybrid mixtures of flammable gas and dust. (15th February 2022) - Ji, Wentao; Wang, Yang; Yang, Jingjing; He, Jia; Wen, Xiaoping; Wang, Yan
Highlights: A dimensionless parameter called sensitivity index was defined, which can be used to quantitatively express the explosion sensitivity of hybrid mixtures. A calculation method for the sensitivity index was established using maximum explosion pressure as well as explosion indices of the flammable gas and dust. A predictive approach for determining variations of the lower explosive limit of hybrid mixtures with sensitivity index was established. The predictive performance of the newly predictive approach was verified using data from other hybrid mixtures. Abstract: In order to study variations of the lower explosion limit associated with hybrid mixtures of flammable gas and dust, four hybrid mixtures of methane/lycopodium, methane/polyethylene, ethylene/lycopodium, and ethylene/polyethylene with various concentration ratios were constructed. The lower explosion limits of these mixtures were measured in a 20 L spherical explosion vessel. According to the experimental results, it was obtained that the lower explosion limits of these hybrid mixtures were decreased by increasing the flammable gas concentration. The two-dimensional coordinate system was divided into explosion area and non-explosion area using the lower explosion limit curve. For different hybrid mixtures, the proportions of the explosion area were different in the two-dimensional coordinate system. The larger the proportion, the greater the explosion sensitivity. Based on this proportionality relationship, a dimensionless parameter called sensitivity index was defined as the ratio of the explosion area to the non-explosion area. The greater the sensitivity index, the greater the explosive sensitivity of the hybrid mixture. According to the relationship between the sensitivity indices of different hybrid mixtures, the influencing factors for the sensitivity index were established, including combustion heat of the flammable gas and dust, chemical reactivity of the flammable gas, as well as dimensionless parameters of dust decomposition characteristics. Considering these influencing factors, a calculation method for the sensitivity index was established using maximum explosion pressure as well as explosion indices of the flammable gas and dust. Through this comprehensive study, a new predictive approach for determining variations of the lower explosive limit of hybrid mixtures with the newly proposed sensitivity index was established. The predictive performance of this newly developed approach was verified using data from other hybrid mixtures.